Historical narratives about the COVID-19 pandemic are motivationally biased - Philipp Sprengholz; Luca Henkel; Robert Böhm; Cornelia Betsch (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
How people recall the SARS-CoV2 pandemic is likely to prove crucial in future societal debates on pandemic preparedness and appropriate political action. Beyond simple forgetting, previous research suggests that recall may be distorted by strong motivations and anchoring perceptions on the current situation. Here, based on four studies across 11 countries (total N = 10,776), we show that recall of perceived risk, trust in institutions and protective behaviours depended strongly on current evaluations. While both vaccinated and unvaccinated individuals were affected by this bias, people who identified strongly with their vaccination status - whether vaccinated or unvaccinated - tended to exhibit greater and, importantly, opposite distortions of recall. Biased recall was not reduced by providing information about common recall errors or small monetary incentives for accurate recall, but partially by high incentives. Thus, it seems that motivation and identity influence the direction in which the recall of the past is distorted. Biased recall was further related to the evaluation of past political action and future behavioural intent, including adhering to regulations during a future pandemic or punishing politicians and scientists. Taken together, the findings indicate that historical narratives about the COVID-19 pandemic are motivationally biased, sustain societal polarization and affect preparation for future pandemics. Consequently, future measures must look beyond immediate public health implications to the longer-term consequences for societal cohesion and trust.
Keywords: C91; D83; D91; 330; Memory; identity; polarization; motivated recall